2005
DOI: 10.1515/znb-2005-0513
|View full text |Cite
|
Sign up to set email alerts
|

Tannins and Flavonoids from the Erodium cicutarium Herb

Abstract: A new depside, erodiol, was isolated and identified from the aerial parts of Erodium cicutarium (Geraniaceae), together with essential compounds such as: geraniin, didehydrogeraniin, corilagin, (-) 3-O-galloylshikimic acid, methyl gallate 3-O-β -D-glucopyranoside, rutin, hyperin, quercetin 3-O-(6"-O-galloyl)-β -D-galactopyranoside, isoquercitrin and simple phenolic acids. Their chemical structures were elucidated by means of spectroscopic (ESI MS, HRESI MS, 1D and 2D NMR) evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
3
16
0
Order By: Relevance
“…The 1 H-NMR spectrum showed two major signals: a methoxyl signal at δ H 3.77, and aromatic protons signal at δ H 7.10 (2H, s, H-2, H-6) while the 13 C-NMR spectrum showed six signals: δ C 146.0 (C-3, C-5), δ C 138.7 (C-4), δ C 121.6 (C-1), δ C 109.7 (C-2, C-6), δ C 167.1 for carbonyl group and δ C 51.8 for methoxy group. The spectra data obtained are in agreement with that of methyl gallate reported by Nishioka et al (1998), and Fecka and Cisowski (2005).…”
Section: Structural Elucidation Of Compounds 1 Andsupporting
confidence: 90%
“…The 1 H-NMR spectrum showed two major signals: a methoxyl signal at δ H 3.77, and aromatic protons signal at δ H 7.10 (2H, s, H-2, H-6) while the 13 C-NMR spectrum showed six signals: δ C 146.0 (C-3, C-5), δ C 138.7 (C-4), δ C 121.6 (C-1), δ C 109.7 (C-2, C-6), δ C 167.1 for carbonyl group and δ C 51.8 for methoxy group. The spectra data obtained are in agreement with that of methyl gallate reported by Nishioka et al (1998), and Fecka and Cisowski (2005).…”
Section: Structural Elucidation Of Compounds 1 Andsupporting
confidence: 90%
“…We tested five different target species of which two responded with significant radicle growth inhibition and a trend for inhibition in a third species was observed. E. cicutarium contains high levels of phenolic compounds (Fecka et al, 2001;Fecka and Cisowski, 2005) in addition to terpenoids, which are also known as allelochemicals (Cheng and Cheng, 2015). It is yet unknown, in which way the concentrations of terpenoids and phenolics are related in E. cicutarium.…”
Section: Monoterpenes and Potential Allelopathymentioning
confidence: 99%
“…The mericarps have been characterized from a mechanical perspective (Evangelista et al, 2011), and experiments demonstrated a positive relationship between fruit (i.e., mericarp: seed plus awn) length and ballistic dispersal (Jacobs and Lesmeister, 2012). Secondly, E. cicutarium contains high levels of specialized metabolites such as phenolic compounds (Fecka et al, 2001;Fecka and Cisowski, 2005) and terpenoids (Radulovic et al, 2009;Stojanovic-Radic et al, 2010), which are constitutively contained at remarkably high levels in plant extracts. Moreover, the plant species has been subject of various invasion ecology studies, as it affects biodiversity and agriculture in its invaded range (Blackshaw and Harker, 1998;Brooks, 2000).…”
mentioning
confidence: 99%
“…[9,15,20] Water and water-acetone extracts of E. cicutarium herb showed the presence of erodiol along with two gallotannins ((À )-3-O-galloylshikimic acid, methyl gallate 3-O-β-D-glucopyranoside), three ellagitannins (didehydrogeraniin, corilagin, geraniin), four flavonoid glycosides (quercetin 3-O-(6'-O-galloyl)-β-D-galactopyranoside, rutin, hyperoside and isoquercitrin) and two phenolcarboxylic acids (gallic acid and protocatechuic acid). [19] Fecka et al [3] found brevifolin, gallic acid methyl ester, gallic acid, ellagic acid and protocatechuic acid to be the main constituents of the Erodium genera, including E. cicutarium herb, and identified brevifolincarboxylic acid as well. Among other identified compounds, there are salicylic acid, m-and phydroxybenzoic acid, 2,3-dihydroxybenzoic acid, gentisic acid, vanillic acid, and hydroxycinnamic acid derivatives: caffeic acid, p-coumaric acid and ferulic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the diverse traditional use into account and, among others, the presence of polyphenolic constituents, it is not surprising that previous experimental studies showed data supporting antioxidant, antimicrobial, spasmogenic, interferonogenic, antiviral and antiproliferative activity. [1,8,12,14,18,19,[21][22][23][24] Although data regarding in vitro antioxidant activity of E. cicutarium can be found in literature, it still lacks a 'whole picture perspective' from a uniform experimental point of view, especially considering the variations in solvent choice and extract preparation conditions that make it rather difficult to compare data published so far. [14,18,19,24] To our best knowledge, most available literature data of antioxidant activity extracts of E. cicutarium are a result of testing activity of ethanol extracts.…”
Section: Introductionmentioning
confidence: 99%